EUTIKHUS YANG TERTIDUR, MATI DAN BANGKIT: PEMBACAAN NARASI KISAH PARA RASUL 20:7-12 MELALUI TEORI OPOSISI NASKAH DAN HUMOR - James A. Lola; Ronaldo Stefanus; Gebi Armianti (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
This study aims to identify and explain the dimensions of humor in the narrative of Eutychus in Acts 20:7–12 and to demonstrate its theological function within the framework of Luke's theology. It uses narrative analysis and a textual opposition approach, a hermeneutical model that emphasizes the identification of tension between normal expectations and narrative reality as a source of humor. The analysis was conducted through a literal reading of the narrative structure, situational irony, and wordplay. The results of the study show that the humor in this passage is consciously constructed through the opposition between the meaning of Eutychus' name (“fortunate”) and his tragic experience, the irony of Paul's long sermon that ended in the death of the listener, and the sudden reversal from tragedy to consolation through resurrection. The humor in this narrative can be seen as a narrative strategy by Luke to teach the theological value of resurrection over death as an important value in Christianity. The use of a textual opposition approach to this text provides an additional alternative for reading and studying the interpretation of scriptural texts, especially narrative texts, to identify nuances of humor, while also showing that humorous narratives can be one model for explaining Christian theological teachings.